Genetic specialization of key bifidobacterial phylotypes in multiple mother–infant dyad cohorts from geographically isolated populations - Aihetanmu, Sainaiwaer; Liang, Zhixuan; Zhang, Xueling; Luo, Baolong; Zhang, Huimin; Huang, Jian; Tian, Fengwei; Sun, Hailong; Ni, Yongqing (Frontiers in Microbiology, 2024)
Little has been known about symbiotic relationship and host specificity for symbionts in the human gut microbiome so far. Bifidobacteria are a paragon of symbiotic bacteria biota in the human gut. In this study, we characterized the population genetic structure of three bifidobacteria species from 58 healthy mother-infant pairs of three ethnic groups of China, geographically isolated, by Rep-PCR, multi-locus sequence analysis (MLSA) and in vitro carbohydrates utilization. One hundred strains tested were incorporated into 50 sequence types (STs), of which 29 STs,17 STs and 4 STs belong to B. longum subsp. longum, B. breve, and B.animalis subsp. lactis, respectively. The conspecific strains from the same mother-child pair were genetically very similar, supporting the vertical transmission of Bifidobacterium phylotypes from mother to offspring. In particular, results based on allele profiles and phylogeny showed that B. longum subsp. longum and B. breve exhibited a considerable intraspecies genetic heterogeneity across three ethnic groups and strains were clustered into ethnicityspecific lineages. And yet almost all strains of B. animalis subsp. lactis were incorporated into same phylogenetic clade regardless of ethnic origin. Our findings support the hypothesis of co-evolution between human gut symbionts and their respective populations, which is closely linked to lifestyle of specific bacteria lineage.Hence, the natural and evolutionary history of Bifidobacterium species would be an additional consideration when selecting bifidobacterial strains for industrial and therapeutic applications.